Consent of Girls in Marriage (A Comparative Study Between Imam Shafi'i and Imam Ibn Qayyim al-Jawziyyah) - Arifin Siahaan; Fandi Wahidi (Jurnal Cendikia ISNU SU, 2025)
There is a difference of opinion between madhhab Shafi'I and Imam ibn qoyyim al-jauzy regarding the law of a guardian asking for his daughter's consent to marry, even though the position of the bride's consent is in place. This research is a literature study using the comparative analysis method. The results of this study show that the most relevant opinion for the Indonesian context is the opinion of Imam Ibn Qayyim al-jauzy.  In the applicable legislation in Indonesia, namely in the law on marriage No. 1/1974 (ps. 6 paragraph (1) jo. ps. 16 paragraph (1) ) KHI stipulates that one of the conditions for marriage is the consent of the prospective bride. This indicates that the applicable legislation in Indonesia is in accordance with the opinion of Ibn Qayyim al-Jawziyyah. In positive law in Indonesia, it is very important and is an absolute requirement for the validity of a marriage. Existing laws and regulations ensure that marriage can only be performed with the free consent of both prospective brides, especially the bride, as part of efforts to protect human rights and ensure justice in the execution of marriage.